Pregled odmevnosti člankov, objavljenih v reviji Zbornik gozdarstva in lesarstva v zbirkah Web of science - Božič, Maja (Acta silvae et ligni, 2013)
The article presents a citation analysis of articles published in the journal Zbornik gozdarstva in lesarstva in the database Web of Science (WoS) throughout the journal's existence, including the year 2011; citations were obtained in February 2013. Journal is not indexed in WoS, therefore, the analysis is focused on citations in journals that are indexed in the database.The purpose of the analysis is to assess the visibility of the journal's articles in science, which is important for the purpose of evaluating research performance and for the journal's editorial policy in the future. From its establishment in 1957 (in 1973 the current title was introduced, while prior to that year the title had been changed twice) and until 2011, which was the last year included in the research, 738 articles were published in the journal. 161 (21.8%) of the articles have been cited 267times in journals that are indexed in WoS. On average, each cited journal has been cited 1.7 times. 34.6% of citations were done by non-Slovene authors. Citations in the database WoS can be found under 21 different variations of the journal's title, which indicates many inconsistencies. Citations of the articles published in Zbornik gozdarstva in lesarstva can be found in 76 different journals, which are classified in 32 different WoS categories; only one third of them is not in any of the three major categories: forestry (37.7%), botany (17.5%) and environmental sciences (10.4%). Inclusion of the journal Zbornik gozdarstva in lesarstva into WoS database, combined with the provision of open access, would probably improve its international visibility.
Keywords: citiranost; bibliometrija; Zbornik gozdarstva in lesarstva; Web of science